Real-time neuropsychological testing during endovascular occlusion of a fusiform aneurysm in the left middle cerebral artery - Barbara Tomasino; Tamara Ius; Benedetto Petralia; Vladimir Gavrilovic; Miran Skrap (Interdisciplinary Neurosurgery, 2019)
Real-time neuropsychological testing (RTNT) was used to test whether permanent endovascular occlusion of the insular branch of the left middle cerebral artery (MCA) helped avoid cognitive and neurological complications following the procedure. This patient suffered from a fusiform aneurysm along the insular branch of the MCA in the territory supplied in the left inferior frontal gyrus, around Broca's area. Pre-intervention neuropsychological testing was normal.During temporary occlusion lasting 25 min, the patient continuously performed at ceiling on the RTNT neuropsychological and language tasks. Thus, permanent occlusion followed. In addition, fMRI was used to investigate changes induced by the procedure. In the language domain, rearrangements in activation in Broca's area and in the left insula were detected by silent and overt production tasks. In the motor domain, decreased activation in the sensorimotor cortex during right-hand movement control was reported along with decreased right-hand sensibility. Post-intervention neuropsychological testing was normal.Results showed that RTNT can be used reliably during temporary occlusion in the specific case of a quite small branch of the MCA to provide continuous feedback on the patient's cognitive and language status and is predictive of post-intervention functioning. In addition, the study enabled us to detect changes in functional organization triggered by temporary occlusion of a branch of the left middle cerebral artery. Keywords: Temporary occlusion testing, Aneurysm treatment outcome, Functional recovery, Inferior frontal gyrus, fMRI, Plasticity, Speech articulation